ARTEMIS: a collaborative framework for health care. - Reddy, R. (American Medical Informatics Association, 1993)
Patient centered healthcare delivery is an inherently collaborative process. This involves a wide range of individuals and organizations with diverse perspectives: primary care physicians, hospital administrators, labs, clinics, and insurance. The key to cost reduction and quality improvement in health care is effective management of this collaborative process. The use of multi-media collaboration technology can facilitate timely delivery of patient care and reduce cost at the same time. During the last five years, the Concurrent Engineering Research Center (CERC), under the sponsorship of DARPA (Defense Advanced Research Projects Agency, recently renamed ARPA) developed a number of generic key subsystems of a comprehensive collaboration environment. These subsystems are intended to overcome the barriers that inhibit the collaborative process. Three subsystems developed under this program include: MONET (Meeting On the Net)--to provide consultation over a computer network, ISS (Information Sharing Server)--to provide access to multi-media information, and PCB (Project Coordination Board)--to better coordinate focussed activities. These systems have been integrated into an open environment to enable collaborative processes. This environment is being used to create a wide-area (geographically distributed) research testbed under DARPA sponsorship, ARTEMIS (Advance Research Testbed for Medical Informatics) to explore the collaborative health care processes. We believe this technology will play a key role in the current national thrust to reengineer the present health-care delivery system.